2014
DOI: 10.1111/jeb.12553
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis and fitness correlates of dynamic carotenoid‐based ornamental coloration in male and female common kestrels Falco tinnunculus

Abstract: Knowledge of the genetic basis of sexual ornaments is essential to understand their evolution through sexual selection. Although carotenoid-based ornaments have been instrumental in the study of sexual selection, given the inability of animals to synthesize carotenoids de novo, they are generally assumed to be influenced solely by environmental variation. However, very few studies have directly estimated the role of genes and the environment in shaping variation in carotenoid-based traits. Using long-term indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Jawor & Breitwisch, 2004;Senar et al, 2008) and is subjected to sexual selection (Badyaev & Hill, 2002;Jawor et al, 2003). Although some have argued that colour traits based on carotenoids reflect foraging ability and territory quality rather than genetic quality (Hõrak et al 2000;Pagani-Núñez et al, 2014), recent studies have shown that carotenoid-pigmented ornaments have a heritable component (Evans & Sheldon, 2012;Vergara, Fargallo & Martínez-Padilla, 2015). In blue tits, yellow breast coloration reflects individual health and parasitism status (del Cerro et al, 2010) and has been associated with provisioning ability (García-Navas, Ferrer & Sanz, 2012) and foraging capacity (Senar & Quesada, 2006).…”
Section: Heterozygosity and Ornamentationmentioning
confidence: 99%
“…Jawor & Breitwisch, 2004;Senar et al, 2008) and is subjected to sexual selection (Badyaev & Hill, 2002;Jawor et al, 2003). Although some have argued that colour traits based on carotenoids reflect foraging ability and territory quality rather than genetic quality (Hõrak et al 2000;Pagani-Núñez et al, 2014), recent studies have shown that carotenoid-pigmented ornaments have a heritable component (Evans & Sheldon, 2012;Vergara, Fargallo & Martínez-Padilla, 2015). In blue tits, yellow breast coloration reflects individual health and parasitism status (del Cerro et al, 2010) and has been associated with provisioning ability (García-Navas, Ferrer & Sanz, 2012) and foraging capacity (Senar & Quesada, 2006).…”
Section: Heterozygosity and Ornamentationmentioning
confidence: 99%
“…Many studies report correlations between plumage color and fitness related traits, including body condition (Siefferman and Hill 2005), mate choice (Hill 1990), and measures of fecundity (Badyaev et al 2001;Safran and McGraw 2004;Siefferman and Hill 2005). Although genetic studies of color variation have increased substantially in the last decade (Fitze et al 2003;Johnsen et al 2003;Hadfield et al 2006;Quesada and Senar 2009;Potti and Canal 2011;Husby et al 2013;Roulin and Ducrest 2013;Vergara et al 2015), few of these consider selection (but see McGlothlin et al 2005;Vergara et al 2015). To understand the evolution of sexually dimorphic coloration, we must quantify both selection and heritability.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies report that bill color is typically brighter or more saturated in the sex with the more ornamented plumage (Alonso-Alvarez et al 2004, Kelly et al 2012, Walsh et al 2012, Cardoso et al 2014, Vergara et al 2015. In birds with sexually monochromatic plumage, males and females often have monochromatic bare parts (Eens et al 2000, Velando et al 2001, Massaro et al 2003, Jouventin et al 2005, Stirnemann et al 2009, Doutrelant et al 2013).…”
Section: Mate Choice For Bare Partsmentioning
confidence: 99%